Gastrokine 1 induces senescence and apoptosis through regulating telomere length in gastric cancer - Yoon, Jung Hwan (Oncotarget, 2014)
The present study aims to investigate whether gastrokine 1 (GKN1) induces senescence and apoptosis in gastric cancer cells by regulating telomere length and telomerase activity. Telomere length, telomerase activity, and hTERT expression decreased significantly in AGS(GKN1) and MKN1(GKN1) cells. Both stable cell lines showed increased expression of TRF1 and reduced expression of the hTERT and c-myc proteins. In addition, TRF1 induced a considerable decrease in cell growth, telomerase activity, and expression of hTERT mRNA and protein. GKN1 completely counteracted the effects of c-myc on cell growth, telomere length, and telomerase activity. Interestingly, GKN1 directly bound to c-myc and down-regulated its expression as well as inhibited its binding to the TRF1 protein and a hTERT promoter. Furthermore, GKN1 triggered senescence, followed by apoptosis via up-regulating the p53, p21, p27, and p16 proteins and down-regulating Skp2. Telomere length in 35 gastric cancers was shortened significantly compared with the corresponding gastric mucosae, whereas GKN1 expression was inversely correlated with telomere length and c-myc and hTERT mRNA expression. Taken together, these results suggest that GKN1 may shorten telomeres by acting as a potential c-myc inhibitor that eventually leads to senescence and apoptosis in gastric cancer cells.